39. Dosimetric study of medical staff for selective internal radiation therapy using 90Y glass microsphere for the treatment of hepatic cancer. (December 2017) - Ralite, F.; Herit, S.; Briceno, P.; Kantor, G.; Cazeau, A.L.; Stein, Ph.; Pottier, V.; Lortal, B.; Catena, V.; Buy, X.; Palussière, J.; Caron, J.
Abstract : Introduction: Selective internal radiation therapy using 90 Y glass microsphere is a treatment dedicated to non-resectable hepatic tumours. This technique requires two imaging modalities, interventional radiology and scintigraphy and handling of two radionuclides. The aim of this work is to assure a safe delivery of this therapy by establishing an average effective dose and an equivalent dose to the extremities for the involved staff for the entire process. Methods: Our study was focused on 5 operators: a radiologist, a nuclear doctor, a radiopharmacist, an interventional radiology (IR) manipulator and a nuclear medicine (NM) manipulator. We considered two phases: the work-up phase that consisting of injecting 99m Tc to check patient eligibility, and the treatment phase with 90 Y microspheres delivery. For both phases, radiopharmaceutical preparation and scintigraphy were performed in the NM department. Three exposure sources were considered: radioscopy, radiography and radionuclides during preparation and injection. The dosimetric evaluations were performed for 5 consecutive patients. Cumulative effective and equivalent (extremities) doses were estimated by dose rate (scopy) and dose (graphy) measurements with an AT1123 radiometer. An Unfors NED dosimeter was used for cumulative hands dose during radioactive source manipulation. Regarding the zoning of operating room, the cartography of cumulative dose carried out for each step. Results: For the entire process, considering all phases and exposition modes, the thorax effective dose (without taking into account the shielded apron) was 1.6 μSv for the NM manipulator, 9.1 μSv for the IR manipulator, 1 μ Sv for the nuclear physician and the radiopharmacist and 21.9 μSv for the radiologist. The equivalent hands dose was 358.4 μSv for the NM manipulator, 3.7 μSv for the nuclear physician, 63.4 μSv for the radiologist and 2.2 μSv for the radiopharmacist. A yellow controlled zone was applied for all the areas of the operating room due to total cumulative doses of 147 μSv and 90 μSv at 1 m from the patient for work-up and treatment respectively. Conclusion: This "operator maximum dose" study suggests that the radiologist and the NM manipulator receive significant exposure on their hands. However it is completely compatible with the personal radiation ranking due to a limited number of RIS performed per year. The determined yellow radiation controlled area is applied to both work-up and treatment phases.